The magnitude of perinatal depression and associated factors among women in Kutaber woreda public health institution and Boru Meda general hospital, Ethiopia, 2022: a cross-sectional study - Seid, Jemal; Mohammed, Emam; Cherie, Nigusie; Yasin, Husnia; Addisu, Elsabeth (Frontiers in Psychiatry, 2024)
Background: Perinatal depression, characterized by the presence of depressive symptoms during pregnancy and/or within the first 12 months postpartum, poses a significant global public health concern. It contributes to a multitude of health risks for mothers, their infants, and their families.Understanding of perinatal depression and its associated factors is crucial for effective prevention and intervention strategies. However, there is a lack of comprehensive research on this topic in Ethiopia. Therefore, this study aims to determine the prevalence and factors contributing to perinatal depression among Ethiopian women.Methods: An institutional-based cross-sectional study was conducted, involving 552 women receiving perinatal services at Kutaber district health institution and Boru Meda General Hospital. Study participants were selected through systematic random sampling techniques. Perinatal depression was assessed using the Depression, Anxiety, and Stress Scale-21 (DASS-21). The associations between various determinants and perinatal depression were examined using binary logistic regression, and factors with a p-value of less than 0.2 were included in the multiple logistic regression analysis. A p-value less than 0.05 was considered statistically significant.The prevalence of perinatal depression was found to be 32.2%. The prevalence of perinatal depression was found to be 32.2%. Factors significantly associated with perinatal depression included being a student (Adjusted Odds Ratio [AOR] = 4.364, 95% Confidence Interval [CI]:1.386, 13.744), experiencing excessive pregnancy-related concerns (AOR = 1.886, 95% CI: 1.176, 3.041), past substance use (AOR = 2.203, 95% CI: 1.149, 4.225), the presence of anxiety symptoms (AOR = 3.671, 95% CI: 2.122, 6.352), experiencing stress symptoms (AOR = 6.397, 95% CI: 3.394-12.055), and daytime sleepiness (AOR = 2.593, 95% CI: 1.558, 4.316).The findings of this study indicate a relatively high prevalence and valuable factors associated with perinatal depression. It highlights the need for a comprehensive approach to perinatal mental health that takes into account not only the biological aspects of pregnancy but also the psychological, social, and lifestyle factors that can impact a person's mental well-being during this critical period.